Strength and stiffness degradation modeling and fatigue life prediction of composite materials based on a unified fatigue damage model. (July 2022) - Gao, Jianxiong; Zhu, Pengnian; Yuan, Yiping; Wu, Zhifeng; Xu, Rongxia
Highlights: A unified fatigue damage model is proposed based on the performance degradation of composites. A pair of residual strength and stiffness models is presented to characterize the degradation rules. Correlation between strength degradation and stiffness degradation of composites is elaborated. Fatigue life prediction methods are developed from the viewpoint of performance degradation. Abstract: The performance degradation of composite materials under fatigue loading is so complex that the present knowledge is far from complete. This study aims to present a pair of residual strength and residual stiffness models based on a unified fatigue damage formula, and predict fatigue life under variable amplitude cyclic loading. Firstly, a unified fatigue damage model for composite materials is proposed, which is capable of characterizing fatigue damage development caused by strength degradation and stiffness degradation, respectively. Subsequently, a pair of residual strength and residual stiffness models is presented to estimate the performance degradation of composite materials. Finally, the corresponding life prediction methods are developed from the viewpoints of strength degradation and stiffness degradation, respectively. A set of experimental data for composite laminates are utilized to validate the proposed models and methods. The results show that the proposed residual strength and stiffness models are flexible enough to fit strength and stiffness degradation data with good agreement. Moreover, the developed life prediction methods are capable of calculating fatigue life of composite laminates with high accuracy.